Answer:
start the solution either by solving the first given equati9on for y or by reducing the second equation by dividing all three terms by 2
Step-by-step explanation:
-2x + y = -1 is most easily solvable for y: y = -1 + 2x.
Note that we can reduce the second equation to 2x + y = 6
Substituting this -1 + 2x for y in this new version of the second equation yields:
2x + (-1 + 2x) = 6
Simplifiying, we get:
2x - 1 + 2x = 6, or 4x = 7. Then x = 7/4.
Again: start the solution either by solving the first given equati9on for y or by reducing the second equation by dividing all three terms by 2.